Innovative Learning Of PAI And Ethics: Social And Religious Skills Of Grade 4 In The Era Of Globalization In Public Elementary School 11 Pontianak Kota - Wahyudi, Annisa Rezki Eka Putri; Rahmatika, Nadiya Ulya; Sukino, Arief; Supriyatno, Triyo (Yayasan Rahmat Islamiyah, 2025)
This study focuses on innovations in Islamic Religious Education and Character Education learning at SDN 11 Pontianak City, which aims to improve students' academic understanding as well as social and religious skills. Referring to the constructivism approach, this study explores the application of interactive and participatory learning methods to face the challenges of the times. The study uses a qualitative method with a case study approach. Data collection techniques include participatory observation, semi-structural interviews, and document studies. Data analysis is carried out through an interactive model that includes data reduction, data presentation, and drawing conclusions with source triangulation validation. The results of the study indicate that innovations in Islamic Religious Education learning at SDN 11 Pontianak City have succeeded in increasing student participation in understanding and applying religious values in everyday life. This learning also supports the development of social skills through active interaction between students and teachers. The implementation of the leadership values of the Prophet Muhammad SAW, such as the characteristics of amanah, shiddiq, fathanah, and tabligh, is a strong foundation in the management of relevant learning.